Schmidt Hammer exposure dating (SHED):Calibration procedures, new exposure age data and an online calculator - Tomkins, Matt D.; Huck, Jonny J.; Dortch, Jason M.; Hughes, Philip D.; Kirkbride, Martin; Barr, Iestyn D. (Quaternary Geochronology, 2018)
Recent research has established Schmidt Hammer exposure dating (SHED) as an effective method for dating glacial landforms in the UK. This paper presents new data and discussion to clarify and to evaluate calibration procedures. These make a distinction between Schmidt Hammer drift following use (instrument calibration), and variation between both individual Schmidt Hammers and between user strategies when utilising age-calibration curves (age calibration). We show that while test anvil methods are useful for verifying that Schmidt Hammers maintain their standard R-values, they are inappropriate for instrument calibration except for the hardest natural rock surfaces (R-values: ≥ 70). A range of surfaces were tested using 3 N-Type Schmidt Hammers, which showed that existing anvil calibration procedures led to consistent overestimation of R-values by up to 17.9%. In contrast, new calibration procedures, which are based on the use of a calibration point which lies within the range of R-values measured in the field [Dortch et al. 2016, Quat. Geochron., 35, 67–68], limit variance to maximum of 4.4% for surfaces typically tested by Quaternary researchers (R-values: 25–60). Moreover, these new calibration procedures are more appropriate for age calibration as they incorporate operator variance through choice of sampling location. New calibration procedures are used to compile an updated age-calibration curve based upon 54 granite surfaces (R 2 = 0.94, p <.01) from across Scotland, NW England and Ireland. The inclusion of a further 29 terrestrial cosmogenic nuclide (TCN) exposure ages extends the calibration period to 0.8–23.8 ka, covering the entire post-Last Glacial Maximum (LGM) history of the British-Irish Ice Sheet. To facilitate comparison between studies, an online calculator is made available at http://shed.earth for Schmidt Hammer instrument and age calibration and SHED exposure age calculation. The SHED-Earth calculator provides a rapid and accessible means of exposure age calculation to encourage wider and ...